Utilization of Loose Parts Media in Enhancing Early Childhood Creativity - N. Nurfita; Septyana Tentiasih (Golden Ratio of Data in Summary, 2026)
Early childhood is considered a golden age, a phase that occurs only once in human development. Therefore, it should serve as a fundamental period that significantly influences an individual’s future growth and development into adulthood. One of the most essential competencies for young children in the 21st century is creativity. Creativity itself refers to a higher-order thinking capacity that reflects an advancement in cognitive processes, characterized by continuity, discontinuity, variation, and integration across developmental stages. It is the ability to produce something new or generate innovation. Children’s creativity can be measured through several indicators that need to be encouraged, based on theories of early childhood creativity. These include: the capacity to produce forms or ideas, a high level of curiosity, the ability to create independently without assistance, the ability to answer simple questions, and a sense of responsibility toward assigned tasks. A child’s continuously developing creative thinking ability will lead to the generation of ideas, the formation of relevant connections, the development of imagination, and the ability to view problems from multiple perspectives. Creativity is not exclusive to gifted individuals; every person has the potential to be creative when provided with an appropriate environment.